Mediasi yang Berhasil dalam Perspektif Yuridis Normatif dan Sosiologis - Indana Zulfa; Moch. Muwaffiqillah (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Mediation is an effort to resolve cases that are integrated with the judicial process. However, successful mediation is often seen only in withdrawing the lawsuit completely and ignoring other things. This research aims to determine the form of successful mediation from a normative juridical and sociological perspective. The research method used by researchers is normative juridical research with a statutory approach, by conducting a comprehensive study of primary legal materials, namely PERMA No. 1 of 2016 concerning Mediation Procedures in Court and secondary legal materials, namely articles about mediation. The research results obtained prove that mediation is a mandate from PERMA No. 1 of 2016 expected to resolve cases without going through examination at trial. Referring to Articles 29, 30, and 31 PERMA No. 1 of 2016, it can be understood that the form of a peace agreement through mediation can be said to be successful not only when the lawsuit regarding the object of the case is completely withdrawn. The withdrawal of some of the defendants and some of the objects of the case can also be said to be successful mediation in normative juridical terms. However, sociologically successful forms of mediation can be seen from the mediation that has been carried out by several Religious Courts in Indonesia which shows that the success of mediation is represented by the withdrawal of the entire lawsuit, although this does not deny the withdrawal of some of the defendants or objects of the lawsuit. However, it is as if the withdrawal of some of the defendants or objects of the lawsuit is considered not the real success of the mediation.